2021
DOI: 10.1186/s12909-021-02738-0
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch of corneal specialists’ expectations and keratoconus knowledge in general ophthalmologists - a prospective observational study in Switzerland

Abstract: Background To assess whether Swiss general ophthalmologists have the minimal keratoconus knowledge that corneal specialists would expect them to have. Methods Corneal specialists defined “minimal keratoconus knowledge” (MKK) with respect to definition, risk factors, symptoms and possible treatment options of keratoconus. A telephone interview survey was conducted among one hundred ophthalmologists (mean age 51.9 years (SD 9.5), 60 % male) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
1
23
1
1
Order By: Relevance
“…To the best of our knowledge, no similar study investigating the knowledge and skills of KC was conducted with optometrists, and only one such study was conducted with ophthalmologists at a tertiary referral centre in Lucerne, Switzerland. 20 The study found that none of the ophthalmologists had minimal keratoconus knowledge (MKK) concerning its definition, risk factors, symptoms and possible treatment options. However, they had a mean MKK of 52%, with a range between 28.6% and 81.0%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no similar study investigating the knowledge and skills of KC was conducted with optometrists, and only one such study was conducted with ophthalmologists at a tertiary referral centre in Lucerne, Switzerland. 20 The study found that none of the ophthalmologists had minimal keratoconus knowledge (MKK) concerning its definition, risk factors, symptoms and possible treatment options. However, they had a mean MKK of 52%, with a range between 28.6% and 81.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection and appropriate management of KC patients require optometrists to be knowledgeable and clinically competent and have appropriate infrastructure. A lack of these will potentially contribute to misdiagnoses and underdiagnoses, 19 , 20 , 21 , 22 with resultant poor prognoses and diminished quality of life of the affected patients. Considering the observed increase in KC cases in these facilities, this study was conducted to establish whether optometrists, as primary eye care practitioners, were sufficiently knowledgeable and skilled in the diagnosis and management of KC.…”
Section: Introductionmentioning
confidence: 99%
“…Different levels of prior knowledge affect the cognitive load of medical students in the use of whole case and series clue case format, thus affecting students' knowledge acquisition or diagnostic accuracy ( Kiesewetter et al., 2020 ). Baenninger et al. (2021) showed that the low recall rate of symptoms and risk factors by Swiss general ophthalmologists leads to relatively few cases diagnosed with keratoconus, which makes patients unable to receive effective and timely care.…”
Section: Theorymentioning
confidence: 99%
“…Whether the appropriate prior knowledge can be activated in time is an important premise to ensure the clinicians to give full play to their clinical and nursing ability. Baenninger et al. (2021) evaluated the possible impact of whether general ophthalmologists in Switzerland have the minimum keratoconus knowledge expected by corneal experts.…”
Section: Introductionmentioning
confidence: 99%
“…However, especially in early stages, keratoconus and other cornea pathologies are hard to detect, making a diagnosis based on these scans extremely difficult. Additionally, according to a study done by the Department of Ophthalmology of the Cantonal Hospital of Lucerne, there is a substantial mismatch between corneal specialists' expectations and keratoconus knowledge in general ophthalmologists 5 . Such a method could help to close those gaps and to establish a baseline diagnosis for corneal diseases.…”
Section: Introductionmentioning
confidence: 99%